Bernie Magruder & the bats in the belfry - Naylor, Phyllis Reynolds (New York : Atheneum Books for Young Readers, 2003)
Many residents of Middleburg, Indiana, are already going crazy from the ever-ringing church bells and now, after a bat is spotted in the hotel run by Bernie's family, they worry that the dangerous Indiana Aztec bat has finally arrived.
Keywords: Church bells -- Fiction; Bells -- Fiction; Bats -- Fiction; Hotels, motels, etc. -- Fiction; Mystery and detective stories; Humorous stories